Long-term Outcome of Incisional Hernia Repairs Using the Erlangen Inlay Onlay Mesh (EIOM) Technique - Ayik, Nizameddin; Klein, Peter; Grützmann, Robert; Demir, Resit (Journal of Surgical Research, 2019)
Background: The objective of this study was to investigate the long-term outcome of incisional hernias treated with the Erlangen Inlay Onlay Mesh (EIOM) repair technique, taking into account recurrence, complications, and patient satisfaction. Methods: A total of 163 patients treated in the surgical department of Erlangen university hospital with the EIOM repair between the years 1996 and 2009 were evaluated retrospectively. Results: The collected data revealed a mean follow-up period of 70 (18-190) months. Incisional hernia recurrence after EIOM repair was observed in 6 (3.7%) patients after a mean observation period of 70 mo (18-190) postoperatively. The recurrence rate increased significantly when the body mass index (BMI) was higher than 32 kg/m2. Here, a recurrence rate of 10.5% for BMI> 32 versus 1.7% with BMI ≤32 was reported. There were no significant differences in hernia recurrence if haven been operated by an assistant under supervision or by a consultant. In regard to patient satisfaction, 91% of patients included in this study were satisfied with the surgical outcome. Conclusions: The EIOM procedure is a safe surgical technique that can be used for the treatment of all, also for giant incisional abdominal wall hernias regardless of the size, BMI, or position of the incisional hernia.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Abdominal incisional hernia; Inlay onlay; Long-term; Open mesh repair; Sublay Erlangen